Shape optimization of MR damper valve for prosthetic ankles using magnetic FEM-GA approach with gait simulation integration - Sachin Kumar; Mittapally Sandeep Reddy; Sujatha Chandramohan (Results in Engineering)
This research provides a new dual-domain optimization and simulation process for improving the performance of magnetorheological (MR) dampers and powered ankle prostheses. In the first step, a shape optimization of the MR damper piston is proposed using a multi-objective function coupled with MATLAB and Finite Element Method analysis in ANSYS-APDL. Differing from previous examples of optimizations that considered geometric changes, the piston profile is defined as a parameterized Bézier curve, where modifications could mitigate magnetic saturation characteristics and maximizing damping performance. The optimization offering a 20 % increase in damping force and a 7.59 % decrease in mass over conventional pistons.Simultaneously, an integrated OpenSim–MSC ADAMS simulation workflow was developed to facilitate a physiologically accurate models based on an individual’s gait. A musculoskeletal model of a below-knee amputee with a powered ankle prosthesis and MR damper, was developed in OpenSim and exported to MSC ADAMS to implement actuator modeling and control. The simulated ankle kinematics and dynamics for prosthetic user aligned closely to normative gait data, providing confidence in the biomechanical realism of the workflow. Ultimately, this process allows for virtual gait testing and a quicker refinement cycle of prosthetic designs based on simulation-based observations.